Pengaruh Penambahan Serat Tebu Terhadap Sifat Fisik Pada Campuran Beton Normal - Ahmad Obi Narman; Zulfikar Djauhari; Reni Suryanita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research aims to study the physical properties of concrete with the use of bagasse. The research consisted of 3 tests, they were porosity, shrinkage, compressive strength. The bagasse used were 0.3%, 0.5% and 0.7% of total weight of coarse aggregate. The specimen was tested at 7, 14, and 28 days. The test result showed that the porosity of specimens containing bagasse were higher than that of the control specimen, BN. The porosity of specimen BST 0.7% was 19.3% higher comparing to that of BN. Furthermore, the compressive test showed that the compressive sthrength specimen BN was 25.653 MPa, it was higher than that of specimens containing bagasse fiber. The concrete shrinkage test showed that the predicted shrinkage according to ACI 209 was higher than that of gained from the direct measurement. The shrinkage value for the ACI 209 method was 218 μm. Based on the results of direct measurement, the highest shrinkage value obtained on specimen containing 0.7% fiber concrete was 88 μm. .Keywords : Bagasse, Porosity, Shrinkage, Compressive Strength